Research on the diluents for liquid storage at 5oC of ram semens - Thu, Do Van; Do, Le Thanh; Anh, Nguyen (Academia Journal of Biology, 2014)
This research was performed on 60 semen samples collected from four Phanrang breed rams at the Sontay goat and rabbit research Centre (Hatay province). After the collection, only the samples with good progressive motion (> 70%) were accepted and diluted into diluents. The finally dilute rate was 1:6 (semen:diluent). The temperature of diluents when they were diluted into the semens was 34oC and the stored temperature was 5oC. Research was performed on four diluents: TR diluent (Tris-citric acid-fructose-egg yolk-penicillin and streptomycin), TR diluent with 1% Glycerol, TR diluent with 5% glycerol and TR diluent with 6% DMSO. The progressive motion, the survival rate and the abnormal rate of spermatozoa were evalued during the storage time. The results showed that the TR diluent had maitained a good viability of spermatozoa. Semens stored in the diluents, which had been added either with 1% glycerol or 6% DMSO, had good viability uper 96 hours. The addition of 5% glycerol into the TR diluent reduced its ability to maitain the viability of permatozoa after 72 hours of storage.